Surreal Dreams of a “Creative City” (or: How Camerimage Festival Tried to Convince Łódź to Stop Worrying and Love Modern Architecture) - Klejsa, Konrad (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
Surreal Dreams of a “Creative City” (or: How Camerimage Festival Tried to Convince Łódź to Stop Worrying and Love Modern Architecture) The study focuses on the architectural projects proposed by the creators of Camerimage festival for Łódź – which is struggling to maintain its position as a “film-friendly” city. A so-called “David Lynch studio” and “Frank Gehry congress center” were preliminarily commissioned by the city, but soon both projects were subjected to heavy criticism from the city council. The author presents the dynamics of the debate and stresses the need for taking into account discussions of the concepts of the “creative class” and the “creative city”.